Investigation of the activity and stability of Pd-based catalysts towards the oxygen reduction (ORR) and evolution reactions (OER) in iron–air batteries1. Issue 32 (10th April 2015) - Alegre, C.; Stassi, A.; Modica, E.; Lo Vecchio, C.; Aricò, A. S.; Baglio, V.
<x xml:space="preserve">Abstract</x> Palladium on carbon has proved to be a suitable bi-functional catalyst for application in the air electrode of a metal–air battery.